-4z(z-7)=0

Simple and best practice solution for -4z(z-7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4z(z-7)=0 equation:


Simplifying
-4z(z + -7) = 0

Reorder the terms:
-4z(-7 + z) = 0
(-7 * -4z + z * -4z) = 0
(28z + -4z2) = 0

Solving
28z + -4z2 = 0

Solving for variable 'z'.

Factor out the Greatest Common Factor (GCF), '4z'.
4z(7 + -1z) = 0

Ignore the factor 4.

Subproblem 1

Set the factor 'z' equal to zero and attempt to solve: Simplifying z = 0 Solving z = 0 Move all terms containing z to the left, all other terms to the right. Simplifying z = 0

Subproblem 2

Set the factor '(7 + -1z)' equal to zero and attempt to solve: Simplifying 7 + -1z = 0 Solving 7 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1z = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1z = 0 + -7 -1z = 0 + -7 Combine like terms: 0 + -7 = -7 -1z = -7 Divide each side by '-1'. z = 7 Simplifying z = 7

Solution

z = {0, 7}

See similar equations:

| -4(3-7x)= | | 6+2y=12.2 | | -6x-12=3x+8 | | 3y-2=2.26 | | 3(x+5)-2x+12= | | 7(314)-75(21)-2(259)=x(10+5) | | -2.22=m/4-5 | | 3[z-(6z+15)+5]=3(z+2) | | 1.3+2.3=2.3-2.3 | | Y+6+y=28 | | 7(314)-75(21)-2(259)=x(3+5) | | 1.2=4s-11.2 | | -7(x-8)=9-6x | | 11w-81=744 | | -8-5n=64+3 | | -2y^2-14y+7=0 | | 8[5-8(x-1)]+7[(5x+6)-8]=11x-341 | | .8=ln(y) | | 0=x^2+2x-63 | | 4x+4x=7x-9 | | 5y(y-2)=6-3y | | 4.7x+2=3.2x-4 | | 40x+4(1.5x)=736 | | 4(x-6)-(x+2)=-12 | | g/6-17=1 | | 4x-3+2=8x-3-x | | -8+2x=4 | | 16=10-1/4m | | graphy=-x^2+4x-7 | | 3(x+2)=4(x-7) | | g/30-980=-954 | | 3t(t-2)=4-2t |

Equations solver categories